SIMPLE TECHNIQUES FOR MAKING BAGLOG HOUSEHOLD SCALE - Sigit Kusmaryanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
ABSTRACTOne success is determined by the oyster mushroom cultivation baglog quality oyster mushroom growing media . Mastery practice of making baglog will greatly assist the maintenance baglog in the next phase to produce the optimal production of mushrooms . with the capability of producing baglog can be used as an alternative attempt to do in a household scale . The following will explain the simple technique of making baglog household but can produce optimal oyster mushrooms and production analysis baglog which can be used as an alternative business find additional revenue .